Leveraging Entrepreneurial Marketing and Customer Orientation: A Moderated-Mediation Model Through Innovation Capability in SMEs Performance - Sam, Toong Hai; Halek Mu'min; Notonogoro , Eka Puspita; Sari, Indri Maya; Pramono, Romy; Hong, Heng Chin (International Review of Management and Marketing, 2026)
This study examines how entrepreneurial marketing and customer orientation influence business performance through innovation capability in Indonesian SMEs, with market turbulence as a moderating factor. Using PLS-SEM analysis with 300 SMEs across West Java Province, we tested a moderated-mediation model grounded in Resource-Based View and Effectuation Theory. Results demonstrate that both customer orientation and entrepreneurial marketing significantly enhance business performance, with innovation capability serving as a partial mediator for both relationships. Innovation capability itself significantly impacts performance, confirming its role as a strategic bridge between market orientations and business outcomes. Surprisingly, market turbulence shows a positive direct effect on performance but fails to moderate the innovation capability-performance relationship, challenging conventional assumptions about environmental uncertainty. The model demonstrates substantial explanatory power for business performance and innovation capability development, with strong predictive relevance across all constructs. However, discriminant validity concerns and high intercorrelations between constructs suggest potential measurement artifacts that may inflate relationships. The identical effects of customer orientation and entrepreneurial marketing on innovation capability raise questions about their theoretical distinctiveness, indicating they may represent variations of general strategic competence rather than separate capabilities. Findings suggest that SMEs benefit from integrated strategic orientations, small enterprises, and though methodological limitations constrain theoretical claims. The study contributes to strategic management literature by demonstrating innovation capability's mediating role while highlighting critical challenges in strategic capability research, particularly the difficulty of achieving construct distinctiveness and the need for more sophisticated analytical approaches.